STRUKTUR KEPEMILIKAN SAHAM, KEPUTUSAN KEUANGAN DAN NILAI PERUSAHAAN (Survey pada Emiten Non Keuangan di Bursa Efek Indonesia) - Suryanto Suryanto (Indonesian Journal of Economics and Business, 2011)
There are three major decisions undertaken by the company through the financial manager's role as an agent hired by the principal of the firm, that is financing decisions, investment decisions, and dividend policy. Agency theory says that in practice  it  will show the differences of interest between the managers and the owners of the company that cause the agency conflict. Ownership structure has contributed to minimize the problems arising from agency conflicts in the firm, namely through increased managerial ownership and institutional ownership.This research has been conducted to examine the impact of ownership structure (managerial ownership and institutional ownership) on financial decisions (financing decisions, investment decisions, and dividend policy) and firm value. This research  has used two models, namely : model 1) examine the effect of ownership structure on financial structure decisions and model 2) examine the effect of ownership structure and financial decisions on firm value.Population in this research are all non-financial emitent listed on the Indonesia Stock Exchange, while the sampling method is cluster random sampling which produces 104 emitents. Data collection method is used pooling the data method and analytical methods used is Least Square.  Based on the results of hypothesis testing, it can be concluded that both models on this research, all predictors simultaneously have significantly effect. First, managerial ownership and institutional ownership have a significant effect on financing decisions. Second, managerial ownership and institutional ownership have a significant effect on investment decisions. Third, managerial ownership and institutional ownership have a significant effect on dividend policy. Fourth, managerial ownership, institutional ownership, financing decisions, investment decisions and  dividend policy have significant effect on the firm value.